MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS 3 MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS CERITA RAKYAT SDN 2 TANJUNG INTEN - Lisa Fitria Dewi; Binti Khoiriyah; Nurkaif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reading skill is a fundamental ability that is very important for elementary school students because it becomes the foundation for understanding various subjects and supports the development of early literacy. However, based on the results of the initial observation in the third grade of SDN 2 Tanjung Inten, students’ reading skills were still relatively low, especially in the aspects of reading fluency, intonation, and pronunciation accuracy. This research aimed to improve students’ reading skills through the implementation of folklore-based learning media that is appropriate to the characteristics of elementary school students. This research used the Classroom Action Research (CAR) approach which was conducted in two cycles consisting of planning, action, observation, and reflection stages, with 17 students as the research subjects. Data were collected through reading skill tests. The data analysis technique used quantitative descriptive analysis to calculate the percentage of learning mastery and qualitative descriptive analysis to analyze the learning process. The results of the research showed an improvement in students’ reading skills from 47.1% in the pre-cycle to 58.8% in Cycle I, and it increased again in Cycle II to 94.1%. The improvement could be seen in the aspects of reading fluency, more appropriate intonation according to punctuation, and clearer word pronunciation. Therefore, the use of folklore-based learning media proved to be effective in improving the reading skills of third grade students at SDN 2 Tanjung Inten.